Quantifying the Impact of 8Ps Learning Model on Grade 12 Students’ Performance in Stationary Points Differential Calculus - Omoniyi , Adebayo Akinyinka; Johnston, Sarah Jane; Jita, Loyiso Currell (Journal of Ecohumanism, 2025)
Differential calculus is a crucial topic in mathematics that helps students hone critical thinking and problem-solving skills. Nonetheless, existing literature reports that grade 12 students frequently encounter challenges learning stationary points, a central concept in differential calculus, owing to the limited effectiveness of traditional teaching methods. To address this concern, this study introduced the 8Ps learning model and examined its impact on student performance in stationary points differential calculus. Grounded in Dewey’s theory of reflective inquiry and experiential learning, this study employed quasi-experimental design of pre-test/post-test, non-equivalent control group. The sample comprised 253 grade 12 students and 8 teachers – 128 students and 4 teachers as experimental group and, 125 students and 4 teachers as control group. A mathematics achievement test was pre- and post-administered to both groups for data to evaluate whether any significant mean differences existed between the experimental group exposed to the 8Ps treatment and the control group taught through traditional methods. Data analysis through descriptive statistics and independent samples t-test yielded significant statistical improvement within the 8Ps group relative to the control group. Findings suggest the prospect of the 8Ps learning model to enhance student performance in stationary points differential calculus. The study recommends incorporating the model into calculus education to increase students’ mathematics learning gains.